Efektivitas Penggunaan Media Google Form dalam Meningkatkan Kemampuan Mufrodat Siswa - Fuady, Siti Tsamrotul; Rohmatul Uyuni, Yuyun; Shalihah, Siti (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
Mastery of vocabulary (lexicon) is a fundamental aspect of learning the Arabic language, as it plays an important role in the development of language skills. However, conventional vocabulary learning still faces challenges in terms of effectiveness and student engagement. This study aims to analyze the effect of using Google Form media on improving the vocabulary learning outcomes of eleventh-grade students at MA Al-Irfan Nusantara. This research employs a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The sample was selected using purposive sampling techniques, consisting of 18 students from the XI Natural Sciences (control) and 18 students from the XI Social Sciences (experiment). Data collection was conducted through tests, questionnaires, and documentation. The research results indicate that the use of Google Forms significantly improved student learning outcomes, with an average post-test score of 81.6 for the experimental class compared to 46.6 for the control class. The results of the paired sample test and independent sample test showed significance (2-tailed Sig.) of 0.000 < 0.05. The implications of this study indicate that Google Forms is an effective learning medium to enhance student engagement and cognitive achievement in vocabulary learning, and it can be used as an innovative alternative in digital-based learning evaluation.